EFEKTIVITAS MODEL DISCOVERY LEARNING PADA MATERI TEKS PROSEDUR MENGGUNAKAN MEDIA AUDIO VISUAL - Hermawan, Dimas (Universitas Tanjungpura, 2024)
Learning is an interaction between teachers and students to achieve various goals, whether academic or nonacademic goals. The learning activities carried out are certainly not separate from various supporting aspects, such as teachers, students, as well as models, materials, and learning media. This study aims to measure the effectiveness of the discovery learning model on procedural text material using audio visual media. This study using a quantitative method with a quasi experimental approach, using a one group pretest-posttest design. The subjects study is the 32 students in the 2023 cohort C of Siliwangi University